2016
DOI: 10.1111/jbi.12770
|View full text |Cite
|
Sign up to set email alerts
|

Genetic discontinuities in a dominant mangrove Rhizophora apiculata (Rhizophoraceae) in the Indo‐Malesian region

Abstract: Aim Population genomics data were used to determine the genetic diversity, genetic divergence and genetic structure of the mangrove, Rhizophora apiculata, across its distributional range and to re-assess the evolutionary processes that shaped its current distribution.Location The Indo-Malesian region section of the Indo-West Pacific region.Methods Next-generation sequencing technology was used to sequence 81 nuclear loci from a pooled DNA sample of 31-44 individuals of Rhizophora apiculata from 11 populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 63 publications
4
53
0
1
Order By: Relevance
“…A clear genetic break in the West Pacific Ocean has also been observed in some other sea-dispersed plants: Rhizophora stylosa (Wee et al, 2015), R. apiculata (Guo et al, 2016), Xylocarpus granatum (Tomizawa et al, 2017) and Sonneratia alba , and in these cases the locations of the genetic breaks roughly corresponded to the one determined for V. marina. The presence of common genetic structure in multiple widespread sea-dispersed species…”
Section: Presence Of a Cryptic Barrier In The West Pacificsupporting
confidence: 63%
See 3 more Smart Citations
“…A clear genetic break in the West Pacific Ocean has also been observed in some other sea-dispersed plants: Rhizophora stylosa (Wee et al, 2015), R. apiculata (Guo et al, 2016), Xylocarpus granatum (Tomizawa et al, 2017) and Sonneratia alba , and in these cases the locations of the genetic breaks roughly corresponded to the one determined for V. marina. The presence of common genetic structure in multiple widespread sea-dispersed species…”
Section: Presence Of a Cryptic Barrier In The West Pacificsupporting
confidence: 63%
“…Recent studies have reported genetic structure within oceanic regions where no apparent barriers exist, suggesting that inconspicuous barriers in the marine environment may exist (Duke et al, ). For example, Wee et al () detected clear genetic differentiation between South East Asian (Japan, Vietnam, Philippine and Indonesia) and Oceanian (Fiji, Vanuatu and New Caledonia) populations in Rhizophora stylosa and Guo et al () detected similar genetic structure in Rhizophora apiculata . As the locations of these genetic breaks might correspond to the boundaries of oceanic currents, Wee et al () suggested that oceanic circulation patterns might have acted as “cryptic barriers.” However, the presence of cryptic barriers has not yet been well examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mangroves, which anchor tropical coastal communities, are particularly vulnerable because they already occupy a niche that is on the extreme margin of the woody plant distribution. We and many others have studied the adaptability of major mangrove taxa as well as their evolutionary diversification (Guo et al, 2016; Urashi, Teshima, Minobe, Koizumi, & Inomata, 2013; Wee et al, *These authors contributed equally to the work. 2015; Xu, He, Guo, et al, 2017;Xu, He, Zhang, et al, 2017;Yang et al, 2017;Zhou et al, 2011).…”
mentioning
confidence: 99%